Health and Welfare of Atlantic Salmon in FishGLOBE V5 – a Novel Closed Containment System at Sea - Lazado, Carlo C.; Stiller, Kevin T.; Shahzad, Khurram; Reiten, Britt Kristin M.; Marchenko, Yuriy; Gerwins, Jascha; Radonjic, Filip Strand; Eckel, Bernhard; Berge, Arne; Espmark, Åsa Maria (Frontiers in Animal Science, 2022)
Closed-containment (CCS) systems offer several advantages in controlling the production environment for Atlantic salmon (Salmo salar) aquaculture, especially at sea, where fish are more exposed to challenging environmental conditions. Here, we report the health and welfare of Atlantic salmon in FishGLOBE V5, a 3500 m3 semi-closed containment system. A group of 200,000 post-smolts was followed from a recirculating aquaculture system (RAS) facility, then for four months in FishGLOBE V5, and three months after release in net pens. Fish samples were collected at four time points during the production period, while water quality was evaluated when the fish were in FishGLOBE V5. The water quality in FishGLOBE V5 was within the recommended range for salmon post-smolts. The mortality rate was 1.4% in FishGLOBE V5 and 4.9% in net pens. There was an increase in the prevalence of eye, snout and dorsal fin damages before the fish left the FishGLOBE V5 phase. The plasma level of magnesium was slightly elevated during this phase as well, indicating osmotic imbalance and stress. Histological evaluation of skin and gills showed sporadic cases of non-specific pathologies. In particular, the transitory stay in FishGLOBE V5 partially improved skin health, but not gill health. Gene expression profiling of some biomarkers showed that rearing fish in FishGLOBE V5 could influence the expression of genes involved in stress response, mucus production, and epithelial integrity. This study documented that rearing salmon for a certain period in FishGLOBE V5 during production affected different health and welfare indicators. These changes should be taken into consideration for the improvement of FishGLOBE V5 as a viable technology for post-smolt production at sea.